Traditional Latvian herbal medicinal plants used to treat parasite infections of small ruminants: A review - Kļaviņa, Alīna (Vet World, 2021)
Numerous treatment agents offering prophylaxis against livestock parasites are commercially available. However, because of increasing antiparasitic drug resistance, the increased popularity of environmentally friendly lifestyle choices, and organic farming, there is more demand for new alternatives to livestock anthelmintic control strategies and medications. It is important to develop antiparasitics that are safe, effective, inexpensive, and environmentally safe. Local, traditional herbal plants such as tansy, mugwort, wormwood, and heather may serve as treatments for intestinal parasites of sheep. This overview provides knowledge of traditional Latvian plants with antiparasitic activities to establish a database for further research to develop new herbal antiparasitic drugs.